Yahoo Web Search

  1. Add 102.7 to both sides (1/(1+ r )) * (29.4/ r ) = 102.7 multiply (1/(1+ r )) * (29.4/ r ) 29.4/[(1+ r )( r )] = 102.7 .... 0 = 102.7r + 102.7r^2 - 29.4 Use the quadratic formula to find r . http://www.purplemath.com/modules/quadform.htm - this site shows the formula...

    1 Answers · Science & Mathematics · 18/10/2009

  2. [( r + 2)^3 - 8] = ( r +2 - 2)(( r +2)^2 + 2( r +2) + 4) = [ r ( r ^2 + 4r + 4 + 2r + 4 + 4)] = r ( r ^2 + 6r + 12) so: 1) lim g ( as r approaches 0) = lim r ( r ^2 + 6r + 12) / r = lim ( r ^2 + 6r + 12...

    1 Answers · Science & Mathematics · 29/03/2009

  3. r = √21 (square root of 21) means a number times itself ( r x r ) equals 21 r = ∛21 (cube root of 21) means a number times itself three times ( r x r x r ) equals 21

    1 Answers · Science & Mathematics · 19/03/2013

  4. q( r ) = r³ + 7r² - 24r + 6 q'( r ) = 3r² + 14r - 24 extreme value if q'( r ) = 3r² + 14r - 24 = 0 r = -6 r = 4/3 q(-6) = 186 q(-8) = 134 q(-1) = 36 conclusion, for r ∈[-8, -1], q_max = 186

    4 Answers · Science & Mathematics · 16/08/2009

  5. Derivative of e^( r /2) with respect to r = d(e^( r /2))/dr =(d(e^( r /2))/d( r /2)) x (d( r /2)/dr) =e^( r /2)x(1/2) =(e^( r /2))/2 Anti-derivative or indefinite integral of e^( r /2): = ∫(e^( r /2))dr = (e^( r /2))/(1/2) = 2e^( r /2) To find the integral...

    2 Answers · Science & Mathematics · 25/08/2010

  6. R is reflexive, because for any x, x^2 ≤ x^2 R is not symmetric. For example, 2R3 but not 3R2. R ...

    1 Answers · Science & Mathematics · 14/04/2015

  7. a) r _u = <1, 0, f_u> r _v = <0, 1, f_v>. So, r _u x r _v |i...b) r _u = <- R sin u sin v, 0, 0> r _v = < R cos u cos v, 0, - R sin v>...

    1 Answers · Science & Mathematics · 28/05/2015

  8. 1 + r + r ^2 + r ^3 + ... + r ^n = [1 - r ^(n + 1)] / (1 - r ), for n >= 0. What we want to do ...be LHS = 1... 1 = 1, and RHS = [1 - r ^(0 + 1)] / (1 - r ) = [1 - r ] / [1 - r ] = 1 So the formula holds true for...

    4 Answers · Science & Mathematics · 13/02/2007

  9. r - 3 = pi(t - 2r) r - 3 = pi(t) - 2pi( r ) r + 2pi( r ) = pi(t) + 3 r (1 + 2pi) = pi(t) + 3 r = (pi(t) + 3)/(1 + 2pi) i am khayyam

    5 Answers · Science & Mathematics · 07/03/2010

  10. R = 2.3log(A1 + 3000) - 5.1 gives ( R +5.1) = 2.3log(A1 + 3000) log(A1 + 3000) = ( R +5.1)/2.3 (A1 + 3000) = 10^[( R +5.1)/2.3] A1 = 10^[( R ...

    1 Answers · Science & Mathematics · 02/05/2011

  1. Ads
    related to: R
  2. fastquicksearch.com has been visited by 1M+ users in the past month

  1. Try asking your question on Yahoo Answers